Diritti e Libertà: Ambiguità e Prospettive - Ottavio De Bertolis (Jesuit University Ignatianum in Krakow, 2017)
The Author in his article takes up the issue of human right and freedom. He analyzes the problem from philosophical and legal points of view. The point of departure is legal reality presented in various documents - legal sources, which are called: declarations of rights, constitutions, or legal instruments and their general understanding among people. From the ambiguity of legal understanding of human freedom, the Author differentiates two essential ones: "freedom from" perceived as space left for individual's autonomy regarding state authorities' interference, from which later in contemporary times human rights and constitutional freedom developed and "freedom to", which is understood as state's duty to provide essential political and economical spheres assuring man a digniﬁ ed life.